Ancient genomes in Southwest China revealed genetic interactions among diverse populations in the historical period - Wen Wan; Huangzhen Huang; Changguo Hu; Xinglong Zhang; Qingting Zhou; Meiqing Yang; Jianxin Guo; Mingxia Xie; Kongyang Zhu; Xiaomin Yang; Hao Ma; Rui Wang; et al. (BMC Biology)
Abstract Background Southwest China has been pivotal for agricultural spread, ethnic formation, and cultural diffusion. However, the genetic diversity and population structure of this area remain insufficiently explored, especially during the historical period. Results Here, we report genome-wide data of eight ancient individuals from the Songshan site in Guizhou dating back to the Song and Ming Dynasty. Our results reveal that most Songshan individuals are closely related to the Yellow River Basin farmers, while also showing significant genetic influences from southern East Asia, including affinities with ancients in Guangxi, coastal Fujian, and Southeast Asia. Additionally, some Songshan individuals displayed a high genetic affinity with local Hmong-Mien populations. Conclusions These findings underscore the complexity of genetic interactions and population movements during the historical period, providing new insights into the genetic landscape and ethnic formation processes in Southwest China.